Look Great, Feel Great : 12 keys to enjoying a healthy life now - Meyer, Joyce, 1943- (New York : Warner Faith, 2006)
Bestselling author Joyce Meyer blends self-help with Scripture as she shares her own struggle to overcome unhealthy living habits as well as 12 keys for restoring all-around health. Our bodies are our God-given instruments for experiencing a fulfilling life, for doing good works, and for spiritual development. God's plan for each of us involves maintaining a sound mind, body, and soul. In her latest book, Joyce addresses the "self-esteem drought" that leads us to bad health habits. She includes practical tools that help make complete self-maintenance an easy part of any daily routine. Offering 12 keys to reclaiming our health through such things as exercise, eating habits, soul care, and responsibility, Joyce reveals how simple the restoration process really is.--From publisher description.
Key 1. Let God do the heavy lifting -- Key 2. Learning to love your body -- Key 3. Mastering metabolism -- Key 4. Exercise -- Key 5. Balanced eating -- Key 6. Water your life -- Key 7. Mindful eating -- Key 8. Curb your spiritual hunger -- Key 9. De-stress -- Key 10. Right vision -- Key 11. Make it easy -- Key 12. Take responsibility.
Includes bibliographical references (p. [191]-192) and index.
Keywords: Health -- Religious aspects -- Christianity